Reassessing Course Outlines for Kindness and Transparency: Some Considerations and Strategies - Carter, Jaclyn; Anselmo, Lorelei; Arshad, Muhammad Adil; Biswas, Sreyasi; Dyjur, Patti; Grant, Kimberley A.; Smith, Erika E.; Usman, Fouzia (Imagining SoTL, 2026)
In a workshop at the 2025 University of Calgary Conference on Postsecondary Learning and Teaching, Catherine Denial demonstrated how her efforts towards learning-focussed kindness are not just philosophical, but also evident in how she shapes her course outlines. As we reflected on this experience, we found ourselves connecting Denial’s work on learning-focused kindness with Winkelmes’ (2019) framework, Transparency in Learning and Teaching (TILT). Here, we propose that together these principles of a pedagogy of kindness and TILT offer thoughtful, pragmatic lenses through which instructors can reflect on assessment design and write their course outlines to support student learning. To do so, we offer several practical strategies for applying the principles of kindness and transparent assessment—from the perspectives of constructive alignment, inclusivity, mental health and well-being, and academic integrity—and provide suggestions for how to communicate them in ways that are consistent with evidence-based best practices of teaching. Not every example will fit in every teaching and learning context, nor will the examples provided address each of these areas exhaustively, but we offer them as starting points for instructors who would like to take steps towards incorporating greater kindness and transparency in their course outlines.